Acousto-holographic investigation of the changes in morphology and cellular biomechanics under oxidative stress - Karavelioglu, Zeynep; Varol, Rahmetullah; Sevgi, Merve; Gencoglan, Gulsum; Esmer, Gokhan Bora; Cakir, Rabia; Basbinar, Yasemin; Uvet, Huseyin (NATURE PORTFOLIO, 2026)
Oxidative stress is an important cellular phenomenon that's necessary for the cell to maintain its metabolic activities but causes adverse complications due to abnormal accumulation. It may cause some changes in the mechanical structure and behavior of the cells by affecting the cell membrane and cytoskeleton structure and triggering apoptosis. Moreover, it's closely related to many conditions such as cancer, neurodegenerative diseases, and aging, making it important to examine and understand this phenomenon very well at the cellular level. This study reports a label-free and contact-free platform to image the morphological and mechanical behavior of live cells using an acousto-holographic microscope. F-actin fluorescence staining and Annexin V-FITC/PI staining were also performed to support our results. Different stages of apoptosis can be morphologically distinguished by our method while mapping the elasticity modulus distribution of the cells. It's found that C2C12 myoblast cells, which initially had the highest elasticity modulus, have less resistance to apoptosis and undergo a more significant decrease in elasticity modulus under oxidative stress. HCT 116 cancer cells, which were the softest at the beginning, experience a weaker decrease in elasticity modulus under oxidative stress compared to C2C12 and HUVEC cells. This supports the resistance of HCT 116 cells against apoptosis.
Keywords: Apoptosis; Cell stiffness; Diagnosis; Drug discovery; Holographic microscopy; MICROSCOPY; STIFFNESS; DEATH; Science & Technology - Other Topics